Knowledge, Attitudes and Behaviors of Women Over 20 Years Old on Cervix Cancer in Istanbul, Turkey - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Purpose: The aim of the study was to evaluate knowledge, attitudes and behaviors of Turkish women over 20 years old on cervix cancer. Materials and Methods: This descriptive study was performed at a primary care center covering 246 women using a questionnaire composed of 3 sections and 38 questions. The data were analyzed using descriptive statistics, chi-square test in univariate analysis and multivariate hierarchical logistic regression analysis. Results: Of the 93.7% women who knew about cervical cancer, 68.0% of them had heard pap smear test and 46.1% had actually undergone a Pap smear once or more throughout their lives. According to the results of the hierarchical logistic regression analysis about factors affecting the Pap smear test; in Model 1, increase in age and education levels, in Model 2 and Model 3 increase in age and cervical cancer information points were determined. The most important information source for cervical cancer was TV-radio/media (59.9%) and health care workers (62.8%) for pap smear test. Conclusions: Although most women have heard of cervical cancer, knowledge about cervical cancer and also Pap smear screening rate are significantly lower. Having Pap smear test for women was affected by age and knowledge level about cervical cancer. Informing women about cervical cancer would be an important intervention.
Keywords: Cervical cancer; Pap smear test; knowledge; screening behavior; Turkey; HUMAN PAPILLOMA-VIRUS; RISK-FACTORS; PAP-SMEAR; TURKISH WOMEN; UNIVERSITY-STUDENTS; HPV VACCINATION; TESTING BEHAVIOR; SCREENING UPTAKE; AWARENESS; THAILAND